Effect of hydrolysed collagen supplementation on knee osteoarthritis: a systematic review - Fonseca, Alexandre Guerreiro da; de Faria Coelho, Carly; Sardinha Leonardo Lopes Martins, Patricia; P. Vieira, Rodolfo; Lopes-Martins, Rodrigo Alvaro Brandão (Manual Therapy, Posturology & Rehabilitation Journal, 2022)
Background: Knee osteoarthritis (KOA) is a burden for the modern society. One of the most important inflammatory conditions of the muscle-skeletal system, KOA is characterized by joint pain, crepitus, local inflammation, tenderness, limitation of movement and effusion with no systemic effects. Bjordal et al. (2004) in a meta-analysis, analyzed more than 13,000 patients regarding chronic inflammatory diseases and the use of non-steroidal anti-inflammatory drugs, including coxibs. In this study, the authors demonstrated that in long-term inflammatory diseases, anti-inflammatory drugs had a slightly superior effect compared to placebo. Oral supplementation with hydrolysed collagen has been proposed as an alternative to treat symptoms. The purpose of this review was to investigate the effects or oral supplementation with hydrolysed collagen in KOA. Methods: Randomized placebo-controlled were searched in different databases, from 2001 to 2021, using the following keywords in titles and abstracts (“knee osteoarthritis” OR “knee arthrosis”) AND (“hydrolysed collagen supplementation”). Results: From 565 articles, only 4 fulfilled the eligibility criteria with variations on the number of subjects, collagen dose and origin, age, and gender of patients, blinding with variation also in the bias criteria. Conclusion The studies are very heterogeneous but reached the same conclusion that oral collagen supplementation may be slightly effective to mitigate KOA symptoms. However, the number of studies is a limitation and no evidence of any possible mechanism is provided. Further studies are needed to investigate the hypothesis.